2020
DOI: 10.1002/pon.5608
|View full text |Cite
|
Sign up to set email alerts
|

Association of supportive care needs and quality of patient‐centered cancer care with depression in women with breast and cervical cancer in Mexico

Abstract: Objective To compare the prevalence of depression, supportive care needs (SC‐needs), and quality of patient‐centered cancer care (PCC‐quality) between women with breast cancer and women with cervical cancer and to assess the association of SC‐needs and PCC‐quality with depression. Methods We conducted a cross‐sectional survey in a public oncology hospital in Mexico City with 247 breast cancer and 165 cervical cancer ambulatory patients aged ≥18 years with at least one hospitalization and ≤5 years since diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…[167][168][169][170] Some retrospective studies on cervical cancer showed that even in tertiary care centers fewer than half of patients received palliative care consultation, and those referred to palliative care were often evaluated late in their disease course. [171][172][173][174][175] Palliative care referral was associated with fewer emergency department visits, inpatient stays, and intensive care unit admissions in the last 30 days of life. Palliative care did not affect chemotherapy or radiation administration within 14 days of death.…”
Section: Supportive Carementioning
confidence: 97%
“…[167][168][169][170] Some retrospective studies on cervical cancer showed that even in tertiary care centers fewer than half of patients received palliative care consultation, and those referred to palliative care were often evaluated late in their disease course. [171][172][173][174][175] Palliative care referral was associated with fewer emergency department visits, inpatient stays, and intensive care unit admissions in the last 30 days of life. Palliative care did not affect chemotherapy or radiation administration within 14 days of death.…”
Section: Supportive Carementioning
confidence: 97%
“…Согласно статистике рака в Корее уровень заболеваемости раком у женщин постоянно растет с 1999 г., на 6,6; 5,3 и 1,9 % при раке молочной железы, раке матки и раке яичников соответственно. В то же время, с развитием современной медицины, выживаемость этих женщин, больных раком, продолжает увеличиваться; относительная выживаемость при раке молочной железы, раке матки, раке яичников и раке шейки матки возросла до 14,0; 5,3; 4,8 % и 1,9 % соответственно [8]. Поэтому возникла необходимость проведения различных мероприятий у женщин, перенесших  SCIENTIFIC REVIEW № 4, 2022   MEDICAL SCIENCES  рак, для адаптации к социальным факторам жизни.…”
Section: результаты исследованияunclassified
“…Тревога и депрессия также являются одними из актуальных психосоциальных проблем у больных гинекологическим раком (шейки, тела матки и яичников) [5,6]. В этом отношении не только медикаментозное лечение, но и социальная поддержка должна быть ключевым инструментом в борьбе пациентов с различными факторами риска как важный вклад в их благополучие [7][8][9].…”
unclassified
“…Health care professionals have the responsibility to promote matching between patients’ supportive care needs and supportive care services for their medical specialty [ 5 ]. Due to the lack of awareness of the active utilization of supportive care services, various unmet supportive care needs of patients with cervical cancer have been exhibited [ 6 ]. A study showed that 88% of long-term cancer survivors (N = 2,107) preferred oncologists to be involved in their cancer follow-up care, but only 60% reported an oncologist visit after treatment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring of interventions to cancer patients’ needs has been argued to be a prerequisite for their successful rehabilitation [ 12 ]. Virtually, the needs management intervention approaches have mainly focused on face-to-face counseling, telephone follow-up, web-based intervention, or the combination of the three and are typically offered by health care professionals [ 6 , 13 ]. Such approaches, although promising, have encountered problems in effectively motivating individual self-management and difficulties in functioning as a navigation instrument for personalized supportive care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%